2012
DOI: 10.1186/1471-2318-12-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social support on cognitive change and mortality in old age: results from the prospective multicentre cohort study AgeCoDe

Abstract: BackgroundSocial support has been suggested to positively influence cognition and mortality in old age. However, this suggestion has been questioned due to inconsistent operationalisations of social support among studies and the small number of longitudinal studies available. This study aims to investigate the influence of perceived social support, understood as the emotional component of social support, on cognition and mortality in old age as part of a prospective longitudinal multicentre study in Germany.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 42 publications
3
27
0
3
Order By: Relevance
“…1821,35 Our study extends these findings to risk of MCI, a pre-dementia based clinical diagnosis. However, our results were unexpected as many studies have found associations between social relationships and cognitive outcomes.…”
Section: Discussionsupporting
confidence: 67%
“…1821,35 Our study extends these findings to risk of MCI, a pre-dementia based clinical diagnosis. However, our results were unexpected as many studies have found associations between social relationships and cognitive outcomes.…”
Section: Discussionsupporting
confidence: 67%
“…financial, emotional, direct help etc.) and each domain might affect cognition differently [32, 71]. It is important to note that our findings do not represent a causal relationship and could indeed be bidirectional.…”
Section: Discussionmentioning
confidence: 96%
“…Yet another publication of the same cohort (Stessman et al, 2005) reported that social factors had the highest correlation with a longer life. It is interesting to compare the findings of the (Jacobs et al, 2011) study to those found in the study reported by (Eisele et al, 2012), where the average age is 82.5 years. The latter is the only cohort study that showed a negative association between social support, understood as the emotional component of social enhancement and cognitive function.…”
Section: Longitudinal Cohort Studiesmentioning
confidence: 88%